Efficacy and safety of low-dose ketamine as an adjunct analgesic and amnesic during caesarean section under general anaesthesia - Sunil Rajan (Indian Journal of Anaesthesia, 2015)
Background and Aims: The practice of avoiding sedatives or anxiolytics during caesarean section under general anaesthesia (GA) until delivery of the baby could result in exaggerated haemodynamic responses and an increased risk of awareness. We aimed to assess the efficacy and safety of low-dose ketamine, used as an adjunct analgesic and amnesic, in attenuating these responses during caesarean section under GA. Methods: This prospective, randomised study was conducted in 40 patients. Group K (n = 20) received 0.25 mg/kg ketamine, whereas Group C received 5 ml normal saline intravenously (IV) just before induction of anaesthesia. After intubation, patients were ventilated with O2and N2O (40:60%) with 0.7% end-tidal isoflurane. Fentanyl and midazolam were given following delivery of the baby. Mann–Whitney and Fisher's exact tests were used for statistical analysis. Results: Preinduction haemodynamic parameters and those recorded at 1 min after induction were comparable in both groups. However, heart rate and systolic blood pressure recorded after intubation (at 3, 5, 7, 9, 12, 15, 20, 30 and 45 min after induction)showed significantly high values in Group C (P < 0.05). Mean arterial pressure also showed a similar pattern. Umbilical vein pO2, pCO2and pH were comparable in both groups. Though Apgar score at 1 min showed a higher scoring in Group K, at 5 min both groups had comparable scores. In Group C, intraoperative lacrimation (50% vs. 0%) and hallucinations/recall of intraoperative events (10% vs. 0%) were high. Conclusion: IV ketamine 0.25 mg/kg can be safely used as an adjunct analgesic and amnesic to attenuate haemodynamic responses during caesarean section under GA without affecting the foetal outcome.